MANAJEMEN PARTISIPATIF DALAM PENGEMBANGAN BUDAYA RELIGIUS PESERTA DIDIK : Indonesia - Iwan Sopwandin; Irawati Dewi; Muhibbin Syah (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2020)
Abstract This study aims to determine the process of participatory management in the development of religious culture in Madrasah Ibtidaiyah Negeri (MIN) 2 Bandung City. This research uses descriptive qualitative method. The type of data collected in this study is qualitative data. The type of data collected in this study is qualitative data. Data collection is done by: a) observation, b) interview, and c) documentation. The results of this study indicate that: 1) The religious culture development program at MIN 2 Bandung, which is the first and most consistent priority, consists of six programs, namely: a) 5S Culture (Smiles, Greetings, Greetings, Polite and Courteous), b) Pray when starting and ending learning, c) Dhuha Prayer, d) Dhuhr Prayer in congregation, e) Tilawah and Tahfidz Al-Qur'an Before learning, f) Infaq every Friday; 2) The implementation or participatory management process in the development of religious culture in MIN 2 Bandung City is indicated by the existence of: a) The existence of participatory leadership, b) The implementation of participatory management indicators, c) The existence of a decision making model, d) The visible implementation of participatory management, e) The existence of participatory management delegation, f) Implementation of delegation procedures, g) Self management team. Keywords: Participatory Management, Religious Culture Abstrak Penelitian ini bertujuan mengetahui proses manajemen partisipatif dalam pengembangan budaya religius di Madrasah Ibtidaiyah Negeri (MIN) 2 Kota Bandung. Penelitian ini menggunakan metode kualitatif dekriptif. Jenis data yang dikumpulkan dalam penelitian ini adalah data kualitatif. Pengumpulan data dilakukan dengan cara: a) observasi, b) wawancara, dan c) dokumentasi. Hasil penelitian ini menunjukan bahwa: 1) Program pengembangan budaya religius di MIN 2 Kota Bandung yang menjadi prioritas utama dan konsisten dilaksanakan terdiri atas enam program, yaitu: a) Budaya 5S (Senyum, Salam, Sapa, Sopan, dan santun), b) Berdoa ketika mengawali dan mengakhiri pembelajaran, c) Shalat Dhuha, d) Shalat Dzuhur berjama’ah, e) Tilawah dan Tahfidz Al-Qur’an Sebelum belajar, f) Infaq setiap hari jum’at; 2) Penerapan atau proses manajemen partisipatif dalam pengembangan budaya religius di MIN 2 Kota Bandung ditunjukan dengan adanya: a) Adanya kepemimpinan partisipatid, b) Dilaksanakannya indikator manajemen partisipatif, c) Adanya model pengambilan keputusan, d) Terlihatnya implementasi manajemen partisipatif, e) Adanya pendelegasian, f) Dilaksanakannya tata cara pendelegasian, g) Self management team. Kata kunci:Manajemen Partisipatif, Budaya Religius